يحي - يحياوي نبيل; أمليلي حميد (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت الدراسة الحالية إلى التعرف العوامل المساهمة في حدوث الإجهاد عند الأساتذة في مرحلة التعليم الابتدائي، وهذا من خلال العمل على محورين المحور الأول خاص بالمفاهيم المتعلقة بالمناهج التعليمية والإجهاد والتعليم الابتدائي أما المحور الثاني فقد تعلق بالمسببات المحتملة لحدوث الإجهاد المتعلقة بالمناهج التعليمية، وهذا باستعمال المنهج الوصفي التحليلي، الذي تم الاعتماد فيه على المصادر والوثائق الرسمية والكتب المدرسية الخاصة بمناهج التعليم في الطور الابتدائي من أجل الوقوف على مختلف الصعوبات والعوائق التي قد تكون عبارة عن عوامل مساعدة في ظهور الإجهاد عند الأستاذ. وبعد تحليل وقراءة الوثائق الرسمية المتعلقة بالكتب المدرسية لمختلف المستويات والأدلّة الخاصّة باستخدام الكتب لكل الأنشطة التعليمية، وكتاب المناهج الخاص باللجنة الوطنية للمناهج سنة 2016 ، والوثيقة المرافقة للمناهج، والمذكرات التوجيهية المختلفة خلصت الدراسة إلى تحديد مايلي لحدوث الإجهاد: تعدّد المصطلحات والمفاهيم البيداغوجية التربوية وغموضها،تعدد الأنشطة في مختلف السنوات، الافتقار إلى التكوين الحقيقي على المناهج التعليمية، تناقض شبكة المواقيت والمخططات السنوية، تعدّد عمليات التقويم، صعوبة تنويع الاستراتيجيات والأساليب التعليمية الحديثة، مشكلة الوسائل التعليمية، الفوارق في المستوى بين التلاميذ بسبب عدم الاستفادة من التربية التحضيرية. Abstract: The current study aimed to identify the factors that contribute to the occurrence of stress among teachers in the primary education stage, and this is through work on two axes. The first axis is related to the concepts related to educational curricula, stress, and primary education, while the second axis is related to the possible causes of the occurrence of stress related to educational curricula, and this is done using the descriptive approach. Analytical analysis, in which official sources, documents, and textbooks for primary education curricula were relied upon in order to identify the various difficulties and obstacles that may be factors contributing to the emergence of teacher stress. After analyzing and reading the official documents related to textbooks for various levels, the guides for using books for all educational activities, the curriculum book of the National Curriculum Committee in 2016, the document accompanying the curricula, and the various guidance notes, the study concluded by identifying the following for the occurrence of stress: The multiplicity and ambiguity of educational pedagogical terms and concepts, the multiplicity of activities in different years, the lack of real training in educational curricula, the inconsistency of the network of annual schedules and plans, the multiplicity of evaluation processes, the difficulty of diversifying modern educational strategies and methods, the problem of educational methods, the differences in level between students due to lack of benefit. From preparatory education.
Keywords: 1الإجهاد; 2 الأستاذ; 3 التعليم الابتدئي; 4 المناهج التعليمية; 5العوامل: 1 1Stress; 2 Professor; 3 Primary education; 4 Educational curricula; 5 factors